2016
DOI: 10.1002/ecs2.1571
|View full text |Cite
|
Sign up to set email alerts
|

Sixty‐year post‐windthrow study of stand dynamics in two natural forests differing in pre‐disturbance composition

Abstract: Citation: Kosugi, R., M. Shibuya, and S. Ishibashi. 2016. Sixty-year post-windthrow study of stand dynamics in two natural forests differing in pre-disturbance composition. Ecosphere 7(11):e01571. 10.1002/ecs2.1571Abstract. We examined the dynamics of stand structure and composition over 60 years in two natural secondary forest plots in central Hokkaido, Japan, that had been severely disturbed by a stand-replacing windthrow in 1954. We determined temporal trends in tree density, species richness, species diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…By 2017, 19 years after the storm, average stem density of shrubs and saplings had declined nearly to original levels. This peak and subsequent decline in the density of shrubs and saplings is a common finding in studies of forests after natural disturbances, although the timing of the peak varies between regions (Heartsill Scalley, Scatena, Lugo, Moya, & Estrada Ruiz, ; Kosugi et al, ; Tremblay et al, ; White, MacKenzie, & Busing, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…By 2017, 19 years after the storm, average stem density of shrubs and saplings had declined nearly to original levels. This peak and subsequent decline in the density of shrubs and saplings is a common finding in studies of forests after natural disturbances, although the timing of the peak varies between regions (Heartsill Scalley, Scatena, Lugo, Moya, & Estrada Ruiz, ; Kosugi et al, ; Tremblay et al, ; White, MacKenzie, & Busing, ; Zhao et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…First, it may take longer than the 19 years in our study for species richness to return to pre‐storm conditions (eg. Kosugi et al, ; Liu, Liu, Skidmore, & Garcia, ; Metzger et al, ). For example in a 60‐year study of two forests in Japan following a typhoon, Kosugi et al () found that species richness peaked 37 years after the storm, before declining gradually.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations